EL ROL CLAVE DE LOS AGENTES COMUNITARIOS DE SALUD EN EL USO DE SERVICIOS MATERNOS EN ENTORNOS RURALES: UN ESTUDIO CUALITATIVO. - Iturrino, Fiorella; Condori, Priscila (Revista Peruana de Medicina Experimental y Salud Pública, 2025)
Objective. To understand the perception of the role of Community Health Workers (CHWs) as facilitators of maternal health service utilization in rural settings. Materials and methods. Semistructured interviews were conducted with 11 CHWs assigned to the Paucara Health Center, selected through theoretical saturation sampling. The data were analyzed using a phenomenological approach, and constant comparison was used to inductively identify emerging themes. Results. The interviews revealed three categories of perceptions: 1. Accompaniment and monitoring: identification of pregnancies, home visits, community awareness, transfers in emergency cases, and challenges such as lack of remuneration and community misunderstandings; 2. Cultural and institutional mediation: integration of traditional practices, respectful treatment, addressing cultural barriers; 3. Management: reporting the situation of pregnant women, training, and communal referral. Conclusions. CHWs perceive their roles as relevant in mitigating social, cultural, and structural barriers in maternal care. This study provides evidence for the design of public policies that can strengthen the recognition and sustainability of the work of CHWs, through an equitable and culturally sensitive model of maternal care.